Gambaran Karakteristik Dan Pengetahuan Ibu Tentang Pemberian Asi Eksklusif Pada Bayi di Puskesmas Doro I - Tiara Septi Putri Sari; Neti Mustikawati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Mother's milk (ASI) is a source of food for babies which is useful for the growth and development of babies. Providing breast milk for 6 months to newborns is the gold standard for baby feeding recommended by WHO. Even though breastfeeding is very important for babies, mothers also often experience failure in providing exclusive breastfeeding. This research aims to describe the characteristics and knowledge of mothers regarding exclusive breastfeeding for babies aged 0-6 months at the Doro I Community Health Center. This research is a descriptive quantitative study, data collection uses Cluster Sampling where the sample is grouped based on region (Posyandu) or population location by 65 samples. This research instrument uses a Knowledge Questionnaire about Exclusive Breastfeeding adopted from (Septianingrum, 2018) consisting of 19 questions. For favorable questions the "correct" answer is given a score of 1 and "wrong" is given a score of 0, while for unfavorable questions the "correct" answer is given a score of 0 and "wrong" is given a score of 1. The instrument is valid with a correlation number (r-count) > 0.444 so it is said to be valid while the Cronbach's Alpha value and reliability are 0.984. The data analysis used was univariate in the form of a percentage frequency distribution. The results showed that all mothers of babies aged 0-6 months at the Doro I Community Health Center (Puskesmas) were all respondents (100%) aged 15-49 years, 23 respondents (35.4%) had a high school education, 58 respondents (89.2) did not work and 46 respondents (70.8%) had ever breastfed. Mothers' knowledge about giving exclusive breastfeeding to babies aged 0-6 months at the Doro I Community Health Center shows that all 65 mothers (100%) of respondents have good knowledge about giving exclusive breastfeeding to babies aged 0-6 months. The conclusion obtained is that mothers' knowledge about giving exclusive breastfeeding to babies aged 0-6 months at the Doro I Community Health Center shows that all respondents, 65 mothers (100%) have good knowledge about giving exclusive breastfeeding to babies aged 0-6 months.